2003
DOI: 10.1038/sj.mp.4001281
|View full text |Cite
|
Sign up to set email alerts
|

Met66 in the brain-derived neurotrophic factor (BDNF) precursor is associated with anorexia nervosa restrictive type

Abstract: Several lines of evidence support a role for brain-derived neurotrophic factor (BDNF) alterations in the etiology of eating disorders (EDs). BDNF heterozygous knockout mice show alterations in eating behavior, increased body weight and adipocyte hypertrophy. BDNF also regulates the synaptic efficiency through the modulation of key neurotransmitter systems previously known to be involved in ED. These findings, together with the fact that this neurotrophin is expressed in the hypothalamus nuclei associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
5
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 29 publications
9
113
5
10
Order By: Relevance
“…If our population (n = 114) was to be compared to this control group, no association would have been observed. The frequency of healthy subjects carrying the Met66BDNF allele seems to differ widely from one country to another, being higher in japanese (41.1 %) than in Italians (29.7 %) or Americans (18.0 %) , and a frequency of 15.2 % has been observed in a Spanish control group (Ribases et al, 2003). Different methods have been proposed to correct for population stratification (Devlin et al, 2001) but an important advantage of the TDT is that it is largely protected from population stratification (Spielman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If our population (n = 114) was to be compared to this control group, no association would have been observed. The frequency of healthy subjects carrying the Met66BDNF allele seems to differ widely from one country to another, being higher in japanese (41.1 %) than in Italians (29.7 %) or Americans (18.0 %) , and a frequency of 15.2 % has been observed in a Spanish control group (Ribases et al, 2003). Different methods have been proposed to correct for population stratification (Devlin et al, 2001) but an important advantage of the TDT is that it is largely protected from population stratification (Spielman et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Case-control studies showed interpopulation variations ranging from no association with eating disorders in a german population (Friedel et al, 2005) and in a dutch population (de Krom et al, 2005), association with different subtypes of anorexia nervosa or bulimia nervosa in Spanish and Japanese samples (Ribases et al, 2003;Koizumi et al, 2004), to association with both eating disorders in a joint analysis of five European countries' populations (Ribases et al, 2004). This last study included a french population of 163 anorexics which showed an excess of Met66BDNF allele, especially in the ANB group, compared to a group of 510 control subjects including 56…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will give here an example of how the behavior of genetically modified animals can inform the search for candidate genes. Observations of altered feeding behavior leading to increased body weight in brain-derived neurotrophic factor (BDNF) knockout mice and reports that intraventricular administration of BDNF in rats resulted in reduced feeding and weight loss prompted Ribases et al (2003) to study the BDNF gene in AN. The investigators observed a strong association between restricting AN, as well as minimum body weight, and an amino acid substitution within the BDNF precursor protein (Val66Met); they replicated the findings in an independent sample (Ribases et al 2005).…”
Section: Animal Models Of Anmentioning
confidence: 99%
“…In fact, several studies have associated this polymorphism with increased susceptibility to anorexia nervosa (Ribases et al, 2003), obsessive-compulsive disorders (Hall et al, 2003), eating disorders (Friedel et al, 2005), depression (Sen et al, 2003), schizophrenia (Skibinska et al, 2004), Alzheimer's disease (Ventriglia et al, 2002), and Parkinson's disease (Momose et al, 2002).…”
Section: Introductionmentioning
confidence: 99%